La ilustración de los cuentos de Perrault: tantas Caperucitas como lobos - Murillo Chinchilla, Verónica (2015)
This article presents a chronological journey through the different illustrations of Charles Perrault’s tale Red Riding Hood, as well as its subsequent version modified by Grimm brothers. The study of drawings and engravings from the first edition in 1695 until 1965 suggests an analysis of the aesthetic and cultural implications found in different artistic proposals.